Sustained Simulation Performance 2014: Proceedings of the joint Workshop on Sustained Simulation Performance, University of Stuttgart (HLRS) and Tohoku University, 2014 - Resch, M.M (Springer, 2015)
This book presents the state of the art in high-performance computing and simulation on modern supercomputer architectures. It covers trends in hardware and software development in general and the future of high-performance systems and heterogeneous architectures in particular. The application-related contributions cover computational fluid dynamics, material science, medical applications and climate research; innovative fields such as coupled multi-physics and multi-scale simulations are highlighted. All papers were chosen from presentations given at the 18th Workshop on Sustained Simulation Performance held at the HLRS, University of Stuttgart, Germany in October 2013 and subsequent Workshop of the same name held at Tohoku University in March 2014.